THE EFFECTIVENESS OF BRAINSTORMING TECHNIQUES TO DEVELOP SPEAKING SKILL OF THE SECOND GRADE STUDENTS OF SMAN 2 MAJENE - Haikal Afdal Ramadhan; Munir Munir; Geminastiti Sakkir (State University of Makassar, 2023)
The research objective was to determine the effectiveness of using Brainstorming Techniques in improving students' speaking skills in this case accuracy, fluency and comprehension. This study uses the pre-experimental research method with one pre-test and post-test group. Research using random sampling technique. The sample of this research was students of SMA Negeri 2 Majene grades 11-4 consisting of 27 students. With several topics that researchers use as instruments in the pre-test and post-test. The result of the increase is proven by the t-test value. The findings state that the t-test is greater than the t-table. This indicates that the use of Brainstorming Techniques is effective in improving students' speaking skills. This means that the use of Brainstorming Techniques is effective in developing students' speaking skills in terms of accuracy, fluency and comprehension in grade 11-4 students of SMA Negeri 2 Majene. Keywords— speaking skill, Brainstorming technique, fluency, Accuracy, comprehensibility